Ferroptosis in lymphoma: Emerging mechanisms and a novel therapeutic approach - Zhou, Qiao; Li, Ting; Qin, Qin; Huang, Xiaobo; Wang, Yi (Frontiers in Genetics, 2022)
Unlike apoptosis, necroptosis, autophagy, and pyroptosis, ferroptosis represents a new type of cell death, which is characterized by iron-dependent lipid peroxidation. This process relies largely on the metabolite reactive oxygen species (ROS), phospholipids containing polyunsaturated fatty acids (PUFA-PL), transition metal iron, intra-, and intercellular signaling events, and environmental stress that regulate cellular metabolism and ROS levels. Recent studies show that ferroptosis plays an important role in tumorigenesis, tumor development, and the treatment of hematological malignancies, including lymphoma. Despite the constant emergence of new drugs, the differences in morphological features, immunophenotypes, biological patterns, rates of onset, and response to treatment in lymphoma pose major therapeutic challenges. Since lymphoma is associated with ferroptosis and shows sensitivity towards it, targeting the potential regulatory factors may regulate lymphoma progression. This has emerged as a research hotspot. This review summarizes the current knowledge on ferroptosis induction and resistance mechanisms, their roles and mechanistic details of ferroptosis in lymphoma suppression and immunity, and finally the treatment strategies for lymphoma by targeting ferroptosis.